"Neue Geber": Perspektiven für die (österreichische) Entwicklungspolitik - Clemens Six; Karin Küblböck; Andrea Perchthaler (Austrian Foundation for Development Research (ÖFSE), 2009)
Der Begriff der "neuen Geber" nimmt gegenwärtig sowohl in der akademisch-theoretischen als auch in der politischen Diskussion eine zentrale Stellung ein. Mit diesem Begriff verbindet sich in vielen Fällen der Eindruck, dass sich durch den politischen und wirtschaftlichen Bedeutungsgewinn der damit bezeichneten Akteure die Spielregeln des Politikfeldes Entwicklungszusammenarbeit grundlegend verändern werden. Das Phänomen der "neuen Geber" muss aus Sicht der internationalen Entwicklungsfragen mehrdimensional betrachtet werden, um die tatsächliche Relevanz dieser Veränderungen adäquat diskutieren zu können. – – The term "new donors" is central in current academic as well as in political debates. This working paper gives an overview over different dimensions of the rise of new donors in development policy - development co-operation as such, increased trade relations, global economic transformation and the increased influence on global governance. The second part of the paper analyses Chinese and Indian activities in selected Austrian co-operation countries. The third part deals with the rising significance of "new" private donors within international development policy, taking the example of private foundations. The increasing influence of those institutions implies a series of challenges for the traditional development co-operation - such as the higher complexity of development co-operation efforts, areas of conflicting interests and questions of democracy.
Keywords: 330